2015
DOI: 10.3389/fnbeh.2015.00227
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity disrupts the adult use of aversive prediction errors to reduce fear in uncertainty

Abstract: Early life adversity increases anxiety in adult rodents and primates, and increases the risk for developing post-traumatic disorder (PTSD) in humans. We hypothesized that early adversity impairs the use of learning signals -negative, aversive prediction errors–to reduce fear in uncertainty. To test this hypothesis, we gave adolescent rats a battery of adverse experiences then assessed adult performance in probabilistic Pavlovian fear conditioning and fear extinction. Rats were confronted with three cues associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 46 publications
6
35
0
Order By: Relevance
“…In the procedure, three auditory cues predict unique foot shock probabilities: danger ( p = 1.00), uncertainty ( p = .375) and safety ( p = .00). Using conditioned suppression of rewarded nose poking as our dependent measure, we have previously found excellent discriminative fear in male and female rats: high to danger, intermediate to uncertainty, and low to safety (Berg et al., ; DiLeo, Wright, & McDannald, ; Ray, Hanlon, & McDannald, ; Walker et al., ; Wright et al., ). Theoretically, +PEs provide an updating mechanism that would permit fear to uncertainty to remain at an intermediate level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the procedure, three auditory cues predict unique foot shock probabilities: danger ( p = 1.00), uncertainty ( p = .375) and safety ( p = .00). Using conditioned suppression of rewarded nose poking as our dependent measure, we have previously found excellent discriminative fear in male and female rats: high to danger, intermediate to uncertainty, and low to safety (Berg et al., ; DiLeo, Wright, & McDannald, ; Ray, Hanlon, & McDannald, ; Walker et al., ; Wright et al., ). Theoretically, +PEs provide an updating mechanism that would permit fear to uncertainty to remain at an intermediate level.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, excessive threat processing is not limited to disorders of anxiety. Adults maltreated as children show exaggerated neural responses to threatening stimuli despite the lack of any clinical diagnosis (Dannlowski et al., ), and our laboratory has shown that early adolescent adversity inflates fear to uncertainty in rodents (Walker et al., ; Wright et al., ). While speculative, the current results offer a potential mechanism by which exaggerated +PE activity in vlPAG neurons could drive excessive fear to ambiguous, threatening cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli can be heard or downloaded at http://mcdannaldlab.org/resources/ardbark. Previous studies have found these stimuli to be equally salient, yet highly discriminable (Berg et al, 2014;Wright et al, 2015;DiLeo et al, 2016;Ray et al, 2018). The 42-min pre-exposure sessions consisted of four presentations of each cue (12 total presentations) with a mean inter-trial interval (ITI) of 3.5 min.…”
Section: Pre-exposurementioning
confidence: 99%
“…Clinical studies demonstrate a strong correlation between early-life experiences and cognitive outcomes later in life. Early-life adversity has been linked to increased risk for AD 12 , PTSD 13 and other adult-onset learning and memory impairments 14 . Rodent models allow for the study of causation; indeed, early-life stress in rats and mice lead to structural atrophy of dendrites, attenuated long-term potentiation, and impaired hippocampus-dependent memory in adulthood [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%